Efektifitas Anthelmintika Ekstrak Etanol Kulit Buah Delima (Punica granatum) terhadap Jumlah Kematian Cacing Ascaridia gallisecara inVitro - Nila Murodah; Sri Mumpuni Sosiawati; Iwan Sahrial Hamid; Setiawan Koesdarto; Rochmah Kurniasanti; Poedji Hastutiek (Universitas Airlangga, 2020)
This research was conducted to determine the anthelmintics effect of peel a pomegranate fruit extract etanol against Ascaridia galli worm in vitro. In this research, using 240 samples of A. galli with length 7-11cm without differentiating sex. The concentration of peel a pomegranate fruit extract etanol for immersing the Ascaridia galli were 10 mg/ml, 20 mg/ml, 40 mg/ml, and 80 mg/ml. Negative control was used PBS. Positif control was used piperazin citrate 10 mg/ml. Observation death A. galli worm and analysis of the data at the 6 hour, 12 hour, 18 hour, 24 hour, 30 hour and 36 hour using ANOVA test and Duncan Range Test. ANOVA result showed significant differences between treatments (p<0,05). Duncan Range Test result showed peel a pomegranate extract etanol 40 mg/ml had anthelmintics effects the 36 hour which comparable with piperazin citrate 10 mg/ml.